Investigation Process on Criminal Actions of Corruption of Village Fund - Siswo De Cuellar Tarigan; Sukarmi Sukarmi (Law Development Journal, 2020)
The purpose of this research To analyze processes investigation of the corruption crime of village funds in Tasikmalaya Regency, which encountered in investigating the corruption crime of village funds in Tasikmalaya Regency, To analyze what solutions investigators took in overcoming obstacles encountered in investigating criminal acts of village fund corruption in Tasikmalaya Regency. The approach method used is juridical normative and juridical socio-logical method, the specifications in the research are descriptive analytical, population and sampling methods are all objects or all symptoms or all events or all units to be studied, data collection techniques use literature study and interviews, data analysis used is qualitative. Research results: Proses investigating the corruption crime of village funds in Tasikmalaya Regency with the existence of a report, the Police carried out a series of investigative actions to find and find an event that was suspected of being a criminal act of corruption in order to determine whether or not an investigation could be carried out in a manner regulated by law. After an investigation is carried out and a criminal act of village fund corruption is found, it is upgraded to an investigation, namely a series of actions by the investigator in terms and according to the manner stipulated in law to seek and collect evidence, which with this evidence makes clear about the criminal act of fund corruption, village that happened and in order to find the suspect. The investigation process extended detention, searches and confiscations. Obstacles faced in carrying out criminal investigations at the Tasikmalaya Police: The suspect did not provide clear information, the witness's statement did not support the implementation of the investigation and the evidence to be submitted was incomplete. Efforts made in overcoming obstacles are as follows: The suspect must provide honest and clear information to the investigator regarding the sequence of events and objects of the criminal act of corruption and where it can be used as evidence to reveal criminal acts of corruption in village funds, Witnesses must be able to cooperate with investigators in provide honest and complete information, making it easier for investigators to uncover criminal acts of village fund corruption, Investigators must be able to find and collect evidence, at least 2 (two) pieces of evidence.